(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, ordering food online from a wide range of restaurants is quite prominent since it is practical and convenient. Various food establishments provide the greatest deals and affordable pricing when delivering food via online services, which led to a development in the food services and food aggregator industries in the Philippines. Food Panda and Grab Food are two major businesses in the country that have established online food delivery services through mobile applications. These applications offer meal menu designs, pricing, and promotions from any restaurant in the locality. In this study, the researchers identified that the most preferred food delivery service is the GrabFood application, and these are the factors that influence customer preferences. Additionally, researchers found the common issues they encountered regarding the application, price, promotions, and service, such as unavailability of the food/restaurant options, promotions having a limited time/slot, and delayed food delivery. The result shows that the quality of the application and service, like the user-friendly app, providing more vouchers and discounts, and the professionalism of the food courier are the most considered factors that influence customer satisfaction and preferences.